Optimization of Land Asset Management in Increasing Locally Generated Revenue - Noor Aulia Rahman; Jusni Ambo Upe; Darmawati Darmawati (Hasanuddin Journal of Business Strategy, 2021)
Mamuju District, located in the Province of West Sulawesi, Indonesia, has a land asset of as many as 1219 fields with the value of IDR.543.600.722.211 which consists of 1216 privately managed fields and 3 cooperation party managed fields. The regional government has managed and utilized the existing asset potential, however, there are still some assets that are not optimized to increase the Locally Generated Revenue of Mamuju. In this research, the study uses a descriptive qualitative approach to describe the facts, situations, and activities from observed objects systematically. The research object is the Regional Finance and Asset Management Agency or called BPKAD in Mamuju District. The results of this research indicated that to increase locally generated revenue, attention should be given to the optimization process comprising of asset management, implementation procedures, and utilization forms. In the asset management aspect, management and control are said optimal. However, planning and organizing are not yet optimal. In the implementation, it is found well done. For utilization, attention should be given to build-operate-transfer, build-transfer-operate, and the Indonesian Trade Union Confederation. In the process of increasing the local revenue, the study also found that there are twelve supporting and resisting factors that could be occurred. Those supporting factors are numbers of lands owned by Mamuju district, ease of asset for legislation and authority, harmony relationship with the province, information technology, agency service capacity, a wide opportunity is offered by the province to optimize land management owned by the district. Further, the study found that the implementation of land asset management could impact the increase of revenue, land prices, improving asset data control, reducing land dispute, optimizing utilization for public service purposes. However, to the last point, the optimization of regional land asset management is not yet done optimally.